How far are the benefits of the Islamic Philanthropy and Social Entrepreneurship movement? - Dwi Saputra, Arief; Rahmatia, Alfina; Muslimah, Muslimah (El-Qish: Journal of Islamic Economics, 2021)
Islamic philanthropy and social entrepreneurship have created solutions in addressing the problems that occur for maximizing economic, social, and religious activity. In this study review, Islamic philanthropy links the elements of zakat, infaq, sadaqah, and waqf in terms of social entrepreneurship with elements of social value, civil society, innovation, and economic activity. The data was obtained using literature studies and interviews on Lazismu Bengkulu as an Islamic philanthropic movement and CV. Presidium on the social entrepreneurship movement. Then, data were processed using Nvivo and drawn conclusions through word similarity analysis. Findings. The synergy between employers and society plays a role in addressing problems against poverty alleviation, wealth equality, community welfare, creating social benefits, optimizing social capital, innovation in problem-solving efforts, building a balance between social activities and business activities. Integration of these two movements explains the dominant increase compared to the decline by presenting an impact on production, consumption, investment, economic growth, and economic stability. In the analysis of word similarity, efforts of synergy and integration concluded that both movements could be implemented in practice because they support each other and have close links to achieve goals and increase the dominant impact of social, economic, and religious activities.